Craniofacial and traumatic brain injuries in mixed martial arts. Issue 4 (2nd October 2021) - Fares, Mohamad Y.; Salhab, Hamza A.; Fares, Jawad; Khachfe, Hussein H.; Fares, Youssef; Baydoun, Hasan; Abboud, Joseph A.; Alaaeddine, Nada
ABSTRACT: Objective : Mixed-Martial-Arts (MMA) has witnessed a rapid growth over the recent years. This study aims to explore the patterns and trends of head injuries in MMA. Design : Descriptive epidemiological study. Setting : Ringside physician reports of the Ultimate Fighting Championship (UFC) fights between 2016 and 2019 (inclusive) were screened. Data were extracted from the Nevada State Athletic Commission (NSAC) database. Play-by-play video analysis was also conducted. Participants : UFC fighters involved in fights sanctioned by the NSAC, between 2016 and the end of 2019 (N = 816). Independent variables : Sex, location of head injury, type of head injury, injury mechanism, number of significant head strikes, type of finish, and weight division. Main outcome measures : Head injury rates were calculated. A one-way analysis of variance (ANOVA) was used to explore any statistically significant differences between injury rates of different locations, types, and types of finishes. An independent t-test was used to determine whether any significant differences existed between the two sexes, and a Joinpoint regression analysis was used to determine the statistical significance of the trends of head injury rates across different weight divisions. P-values <0.05 were considered significant (95% CI). Results : A total of 288 head injuries in 408 fights were recorded during our study period. Head injury rate constituted 35 injuries per 100 athletic-exposures (AE) in sanctioned fights. Traumatic brain injuries (TBI) were the most common type of injury, with a rate of 16 per 100AE, significantly greater than that of fractures (p = 0.003). Males had a head injury rate of 37 per 100AE, higher than that of females which was 23 per 100AE. Technical Knockout (TKO)/ Knockout(KO) was the type of finish with the highest rate of head injuries, significantly greater than that of decision or submission (p < 0.001). In general, head injury rates were higher as weight divisions increased. Conclusion : Head injuries are prevalent in MMA. Preventive measures need to be implemented to ensure fighter safety and limit injury risk.